Diseño de un manual específico de control interno para microcréditos en la Cooperativa de Ahorro y Crédito Virgen del Cisne, agencia La Maná, provincia de Cotopaxi, año 2010 - García Soria, Safira Elizabeth (2012)
The conducted research has as main objective not only to provide to the area of micro-credits a management tool for improving the development of the staff but also to facilitate the process of granting micro-credits and obtain greater efficiency and effectiveness in order to solve problems such as lack a manual of internal control that specifies the duties and responsibilities in the area of microfinance, institutional neglect, lack of a plan for ongoing training and motivation to create a culture of service, lack of induction to the workplace, little attention to the fulfillment of the plan of action to be competitive….